2021
DOI: 10.1039/d1nr02584h
|View full text |Cite
|
Sign up to set email alerts
|

Employing defined bioconjugates to generate chemically functionalised gold nanoparticles for in vitro diagnostic applications

Abstract: Novel methods for introducing chemical and biological functionality to the surface of gold nanoparticles serve to increase the utility of this class of nanomaterials across a range of applications. To...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…through decorating gold nano-particles with IgG antibodies). 5 This work, and the technology that it enables, demonstrates significant advantages of the oriented approach to nanoparticle-protein synthesis, with bromopyridazinedione derivatives playing a key facilitating role.…”
Section: Orientated Nanoparticle-antibody Decorationmentioning
confidence: 88%
See 2 more Smart Citations
“…through decorating gold nano-particles with IgG antibodies). 5 This work, and the technology that it enables, demonstrates significant advantages of the oriented approach to nanoparticle-protein synthesis, with bromopyridazinedione derivatives playing a key facilitating role.…”
Section: Orientated Nanoparticle-antibody Decorationmentioning
confidence: 88%
“…Another key application that has benefited from employing PD-based bioconjugation strategies, is the formation of nanoparticle-antibody conjugates. 5,61,62 DiBrPDs in particular have been used extensively to site-selectively re-bridge antibody-fragments, which can then be attached to the surface of nanoparticles through efficient copper free "click" chemistries. Previous reports have shown that antibody-nanoparticle conjugates synthesised with antibody fragments (e.g.…”
Section: Orientated Nanoparticle-antibody Decorationmentioning
confidence: 99%
See 1 more Smart Citation
“…1). [10][11][12] Key reactions of bioorthogonal chemistry include Staudinger ligation or native chemical ligation, strain-promoted [3 + 2] azide-alkyne and alkyne-nitrone cycloaddition (SPAAC and SPANC) reaction, dienophile and tetrazine inverse electrondemand Diels-Alder (IEDDA) ligation, oxime, and hydrazone ligations along with photoinducible bioorthogonal reactions. 4,13 As such, the IEDDA ligation techniques are quite promising and have been applied in various fields.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, gold NPs are unstable in complex systems, resulting in emerging difficulties in practical analysis and testing. [10][11][12] In case of nonspecific aggregation, gold NPs are normally prepared in the presence of stabilizers, such as small molecules, 13 proteins, 14 nucleic acids, 15,16 polymers, 17 and inorganic materials, 18,19 and LSPR performances promote a broad range of applications. [20][21][22] Nevertheless, even though gold NPs can be stabilized by chemical ligands, slight changes in colorimetric signals are still recorded when nanoprobes are added in these complex samples.…”
Section: Introductionmentioning
confidence: 99%